2021
DOI: 10.1111/iji.12566
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of associations between HLA and renal function

Abstract: Introduction: Kidney dysfunction is a highly significant disease, both in the United Kingdom and globally. Many previous studies have reported associations between human leukocyte antigens (HLA) and renal function; this systematic review attempts to identify, summarize and appraise all published studies of these associations.Methods: A literature search was performed using Medline, Embase and Cochrane Central Register of Controlled Trials to identify papers whose keywords included each of the following concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…An association between HLA-DRB1*11 and ESRD was reported in Taiwanese, Chinese, and Romanian populations [27,36,37]. Only [24,38].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An association between HLA-DRB1*11 and ESRD was reported in Taiwanese, Chinese, and Romanian populations [27,36,37]. Only [24,38].…”
Section: Discussionmentioning
confidence: 95%
“…The classification of primary glomerulonephritis is debatable and confusing. A major cause of confusion is the poor correlation between histological and clinical findings, which generates considerable overlaps between diseases defined by clinical features and diseases defined by histological features [24].…”
Section: Discussionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA)-DRB1 is the most important genetic risk factor for RA. Many studies have reported the association of HLA polymorphisms with susceptibility to RA [12][13][14] or CKD [15,16]. Different DRB1 alleles associated with RA are dependent upon various ethnicities: DRB1*04:01 is associated with European RA [12], and DRB1*04:05 is associated with Japanese RA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these amino acid residues were previously reported to have a significant association with kidney disease. 8…”
mentioning
confidence: 99%
“…Interestingly, these amino acid residues were previously reported to have a significant association with kidney disease. 8 Little is known about PLEKHA5, which is highly expressed in kidney, heart, and other organs. Previous studies have revealed the association of this locus with anthropomorphic traits.…”
mentioning
confidence: 99%